Analysis Of Fabrics Used In Designing Modern Backpacks For School Students. (Eurasian Medical Research Periodical, 2025)
In order to design modern backpacks that meet local conditions and requirements, the fabrics used in the production of backpacks and their characteristics are analyzed in the article. Advantages and disadvantages of fabrics are compared according to the purpose of use.